How is Perseveration in Dysgraphia Students? A Research at Yayasan Pantara Jakarta - Meiyanti Nurchaerani; Syahiid Hidayatullah Rizkyka Hartadhi; Alfian Alfian; Irma Savitri Sadikin (Pedagonal : Jurnal Ilmiah Pendidikan, 2022)
This research focused on handwriting disorders for dysgraphia students. The objective of this research are to analyze and to describe the types of perseveration and types of error in perseveration of 10 dysgraphia elementary school students. This research uses descriptive-qualitative method The data collection technique is from the worksheet that provided to students fill out. Research result discovered there were some perseveration types in dysgraphia found in elementary school students of Yayasan Pantara Jakarta. In this study, only one perseveration type is founded and the type was “Substitution”. The discussion of perseverations part involves ten words. Some students use misspelled words when they confuse one or more characters with different characters. This study also found that it is important to note that most of students have no problem in writing the first letter of a word, the error usually occurs on the next consecutive letter. it can be concluded that there were dysgraphia occure in elementary school students.